AB0034 IFN-Gamma-Producing VZV-Specific CD4 T-Cells in Patients with Rheumatoid Arthritis (RA). (10th June 2014) - Almanzar, G.; Bienenstein, E.; Höfner, K.; Schmalzing, M.; Tony, H.-P.; Liese, J.; Prelog, M.
Abstract : Background: Varicella-zoster-virus (VZV) establishes a life-long latent infection with risk of reactivation in patients with autoimmune disorders receiving immunosuppressive/immunomodulatory therapy. Objectives: The study was aimed to evaluate the VZV-specific cellular immune response in the presence of cytokine-blocking antibodies in rheumatoid arthritis (RA) patients and healthy controls (HC). Methods: IFNgamma- and IL-6-producing-CD4+ and -CD8+ T-cells were determined following stimulation with VZV-antigen in the presence of anti-IL-6 or anti-TNFalpha antibodies in vitro. Intracellular cytokine production was determined by flow cytometry in RA patients and HC. Results: No differences in the IFNgamma- and IL-6-producing CD4+ or CD8+ T-cells were found between RA and HC following VZV stimulation. In the presence of anti-IL-6 in vitro, VZV-specific CD4+ T-cells producing IFNgamma reduced in RA compared to HC (11.0% versus 7.9%). In the presence of anti-IL-6, VZV-stimulated cells showed a reduction of IL-6-producing-CD4+ T-cells compared to cells stimulated with VZV alone in RA (7.2% versus 4.8%). No differences were observed in CD8+ T-cells in RA or in CD4+/CD8+ T-cells in HC. In the presence of anti-TNFalpha in vitro, IL-6-producing-CD4+ T-cells of RA patients were lower following stimulation with VZV compared to HC (6.2% versus 9.2%). Conclusions: The reduction of the CD4+ cellular immune response to VZV by blocking of TNFalpha and IL-6 in vitro suggests an important role of inflammatory cytokines in the modulation of the T-cell response to VZV in RA. The influence of different cytokines on the long-term anti-VZV cellular immunity in patients with autoimmune conditions may need further investigated to prevent VZV reactivation. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5781